2014 IEEE International Electric Vehicle Conference (IEVC) 2014
DOI: 10.1109/ievc.2014.7056123
|View full text |Cite
|
Sign up to set email alerts
|

Flexray versus Ethernet for vehicular networks

Abstract: Data Distribution Service (DDS) middleware has become one of the best solutions for real-time distributed industrial systems. An interesting innovation would be the use of the DDS middleware on top of Ethernet networks to enhance the performances of automobile applications. In this paper, we will introduce the use of DDS on top of Ethernet networks and propose as a testing application an extended SAE (Society of Automotive Engineers) benchmark. The main aim is to be able to calculate the worst case response ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In STL, with the tremendous rise in the number of sensors deployed in the road, the number of connected vehicles and their ever-increasing mobility, the support for low latency and uninterrupted communication between the sensors and the fog is crucial to assure the correct operation of the applications [23]. DDS has been used as basis for improving the network semantics and the QoS in these environments [78].…”
Section: Network Semanticsmentioning
confidence: 99%
See 2 more Smart Citations
“…In STL, with the tremendous rise in the number of sensors deployed in the road, the number of connected vehicles and their ever-increasing mobility, the support for low latency and uninterrupted communication between the sensors and the fog is crucial to assure the correct operation of the applications [23]. DDS has been used as basis for improving the network semantics and the QoS in these environments [78].…”
Section: Network Semanticsmentioning
confidence: 99%
“…Hence, it is necessary to decide which protocol to use in relation to the type of application, adopting MQTT for reliable communications or for big-size packet communication, and CoAP otherwise, in order to decrease latency and increase system performance. DDS is widely used for real-time M2M communications among constrained devices [78]. [78] addresses DDS as one of the best solutions for realtime distributed industrial systems.…”
Section: Low-latencymentioning
confidence: 99%
See 1 more Smart Citation
“…Amel B.N. et al [29] showed how to use DDS over an Ethernet network and proposed a SAE benchmark as a test application. The main goal is to calculate the worst-case response time (WCRT) based on the scheduling model and the use it as a metric to evaluate the DDS real-time QoS (Quality of Service).…”
Section: Vehicle Protocolmentioning
confidence: 99%